Thiamine and riboflavin contents of various flour types produced in different region of Turkey - Raci Ekinci; S. Sezgin Ünal (Pamukkale University Journal of Engineering Sciences, 2002)
In this study, thiamine and riboflavin values of 86 wheat flour samples (30 Type 550, 30 Type 650 and 26 Type 850) from 30 different factories in 19 different city of 7 different region of Turkey were examined. Significant differences in average thiamine and riboflavin values were observed among 86 flour samples in term of flour types. Variations among flour samples from different factories in thiamine and riboflavin values were not found at significant level statistically (P < 0.05). The highest thiamine and riboflavin values were found in the flour samples belong to the region of East Black Sea but not at statistically significant levels. The differences were significant for the flour type at statistically level. The vitamin contents increased together with flour extraction rate and ash content.